Impact of right ventricular involvement on the prognosis of takotsubo cardiomyopathy. (15th June 2015) - Kagiyama, Nobuyuki; Okura, Hiroyuki; Tamada, Tomoko; Imai, Koichiro; Yamada, Ryotaro; Kume, Teruyoshi; Hayashida, Akihiro; Neishi, Yoji; Kawamoto, Takahiro; Yoshida, Kiyoshi
Abstract: Background: Previous studies showed that patients with takotsubo cardiomyopathy had a higher long-term mortality rate than the general population and the incidence of in-hospital complications was higher in takotsubo cardiomyopathy with than without right ventricular (RV) involvement. This study was performed to investigate the long-term prognostic impact of RV involvement in takotsubo cardiomyopathy. Methods and results: The clinical data of 113 patients (72.7 ± 11.4 years old, 84 females) with takotsubo cardiomyopathy were studied retrospectively. The patients were divided into two groups according to the presence (biventricular group, n = 21, 18.6%) or absence (classical group, n = 92, 81.4%) of RV involvement assessed by initial echocardiography. The end point was a composite of all-cause death, re-hospitalization due to heart failure, and recurrence of takotsubo cardiomyopathy. The in-hospital mortality rate was significantly higher in the biventricular group than the classical group (14.3 vs. 1.1%, respectively, P = 0.02). Kaplan–Meier analysis indicated a significantly lower event-free survival rate in the biventricular group than the classical group (log-rank, P < 0.001). On multivariate analysis, RV involvement was the only independent predictor of the end point (HR: 2.73, P = 0.026). Conclusion: The rates of in-hospital and long-term events were significantly higher in takotsubo cardiomyopathy with than without RV involvement, and RV involvement was the independent predictor of the poor prognosis.